An integrated GIS-based Ordered Weighted Averaging analysis for solar energy evaluation in Iran: Current conditions and future planning. (June 2019) - Firozjaei, Mohammad Karimi; Nematollahi, Omid; Mijani, Naeim; Shorabeh, Saman Nadizadeh; Firozjaei, Hamzeh Karimi; Toomanian, Ara
Abstract: Solar energy is one of the important energy sources and countries have realized the important role of renewable energies due to the depletion of conventional energy sources. In this study, a GIS-based analysis is utilized for investigating the feasibility of solar energy in Iran. To evaluate the concept of risk into the GIS-based analysis for determining optimal areas for installation of solar power plants an Ordered Weighted Averaging (OWA) approach is used for the first time. Integration of OWA-based approach and GIS analysis provide models that determine the priority of regions from risk-free decision to risky decision strategies. The results show that Kerman, Yazd, Fars, Khuzestan, Sistan and Baluchistan, South Khorasan and Isfahan provinces have a good capacity to invest in solar energy projects. The GIS-based analysis indicates that the values of installed solar power plants percentages in high chosen areas for the most pessimistic and optimistic strategies are 7% and 64%, respectively. Highlights: A new model is used to evaluate the solar energy in Iran. To evaluate solar energy potential a risk analysis is added to GIS-based method. An Order Weight Averaging is utilized for first time in solar energy assessment. A location analysis is done for currently working solar plants. A maximum of 498 W/m 2 solar radiation is achievable yearly.